(untitled) (Journal of the College of Basic Education, 2024)
Signs: They are local signs that are not separate from the act of uttering, which is an act that requires a utterer to direct his speech to an addressee within a specific temporal and spatial framework. Therefore, it is not possible to assign a meaning to a specific utterance without stopping at the signs on the one hand, and the context of the production of the utterance on the other hand. Signs depend initially on words that bring meanings or connotations, and these signs are the ones that have been counted by philosophers of language and linguists or linguists in all languages. So the expressions of signs are confined to: (I, here, and now) and their significance is used according to the intent. Signs are: expressions that refer to the components of the communicative context (their interpretation dispenses with it), namely the speaker, the listener, the time and place of the utterance, etc.